Jordanian Legislative Elite and Wadi Araba Treaty - Al-Jbali, Sager; Al-Dajah, Hasan (Dirasat: Human and Social Sciences, 2021)
This study aimed at studying the relationship between the Jordanian Legislative Elite and its adoption of Wadi Araba Treaty, either by consent or rejection. The descriptive analytical method was employed to study the relationship between the influential different variables of the Twelfth parliament members stands, due to significance of consistent of this self-elite and its influence on the political behavior of its members. Employing the theory and approach of the applied elite. It is meant by the elite members of the Twelfth Jordan parliament, amounting (80) representatives who voted for Wadi Araba Treaty. With agreement of (55) votes, opposition of (23) votes and abstention of a member and absence of another from voting. The study showed the relationship of factional belongingness and parliamentary coalition for the members of Jordan legislative elite and adoption of the Treaty by the member, and there is a relationship between (the economic-social) characteristics of elite members and adoption of the Treaty; for members of legislative elite from faction with Islamic, national, socialistic, and Ba’thi trend had opposed the Treaty., The rate of support among parliamentary members with military background is more than it at parliamentary members with civilian background.